Mixed Th1 and Th2 Mycobacterium tuberculosis-specific CD4 T cell responses in patients with active pulmonary tuberculosis from Tanzania. - Patrizia Amelio; Damien Portevin; Klaus Reither; Francis Mhimbira; Maxmillian Mpina; Anneth Tumbo; Beatrice Nickel; Hanspeter Marti; Stefanie Knopp; Song Ding; Adam Penn-Nicholson; Fatoumatta Darboe; et al. (Public Library of Science (PLoS), 2017)
Mycobacterium tuberculosis (Mtb) and helminth infections elicit antagonistic immune effector functions and are co-endemic in several regions of the world. We therefore hypothesized that helminth infection may influence Mtb-specific T-cell immune responses. We evaluated the cytokine profile of Mtb-specific T cells in 72 individuals with pulmonary TB disease recruited from two Sub-Saharan regions with high and moderate helminth burden i.e. 55 from Tanzania (TZ) and 17 from South Africa (SA), respectively. We showed that Mtb-specific CD4 T-cell functional profile of TB patients from Tanzania are primarily composed of polyfunctional Th1 and Th2 cells, associated with increased expression of Gata-3 and reduced expression of T-bet in memory CD4 T cells. In contrast, the cytokine profile of Mtb-specific CD4 T cells of TB patients from SA was dominated by single IFN-γ and dual IFN-γ/TNF-α and associated with TB-induced systemic inflammation and elevated serum levels of type I IFNs. Of note, the proportion of patients with Mtb-specific CD8 T cells was significantly reduced in Mtb/helminth co-infected patients from TZ. It is likely that the underlying helminth infection and possibly genetic and other unknown environmental factors may have caused the induction of mixed Th1/Th2 Mtb-specific CD4 T cell responses in patients from TZ. Taken together, these results indicate that the generation of Mtb-specific CD4 and CD8 T cell responses may be substantially influenced by environmental factors in vivo. These observations may have major impact in the identification of immune biomarkers of disease status and correlates of protection.